Evaluating the impact of urban landscape elements on the sense of security and local belonging-case study: Tongdejie, China - Zhu, Yue; Du, Ruichao (Frontiers in Environmental Science, 2024)
The urban landscape as one of the shaping elements of the urban space and a part of physical perception leaves a significant impact on the desirability or undesirability of the urban space. Urban space has the most connection with people and living environment, and as a result, it plays a significant role in giving identity and feeling of peace to citizens. Security is also considered as one of the basic needs in the urban structure, which becomes more important with the expansion of the urbanization process and the increase in population density. If the image of urban spaces is confusing, hateful or monotonous, it has an adverse effect on the citizens and their feelings and reduces the sense of security. Also, the urban landscape is a tool that can have a positive impact on urban life by planning for its optimal design, increasing the sense of belonging of citizens to the city and the surrounding envi-ronment. In this research, the relationship between the urban landscape components on the sense of local belonging and the relationship between the sense of security and the urban landscape was investigated. Based on the results, sense of local belonging and sense of security had a positive and significant correlation. Therefore, living in a safe, attractive and desirable environment creates and strengthens the feeling of belonging to the envi-ronment. Strengthening the feeling of belonging to the environment will increase the satisfaction of the residents and will increase the quality of life in the cities.